Novel therapeutic approaches for gastrointestinal malignancies - Nagaraju, Ganji Purnachandra; Peela, Sujatha; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2020)
This book provides an up-to-date overview of gastrointestinal malignancies, including prevention, early detection, intervention, and life-extending therapeutics. It also assesses various biomarkers used for diagnostics, prognostics and prediction of response to chemoresistance. Further, it discusses the latest trends in the use of small-molecule targeted therapies and immunotherapies as single agents or combination with other treatments. Since resistance to radiation and chemotherapy contribute to the high recurrence and poor survival rates, improving the outcome for GI malignancies is dependent on the introduction of new biomarkers and therapeutic agents. Lastly, the book systematically investigates novel theranostics approaches using nanotechnology for the detection, diagnosis, and personalized treatment of GI malignancies.
Chapter 1. Role of selected transcription factors in pancreatic and colorectal cancer growth and metastasis -- Chapter 2. Adiponectin in gastrointestinal malignancies -- Chapter 3. Small molecule-targeted therapies for GI cancers: success and failures -- Chapter 4. Epigenetic biomarkers for the detection of Gastrointestinal Cancers -- Chapter 5. CD151: A Lateral organizer and modulator of Tumor microenvironment in gastrointestinal cancers -- Chapter 6. Targeting Pathways in GI Malignancies -- Chapter 7. Identification of Potential Key Genes Involved In Progression of Gastric Cancer Using Bioinformatics Analysis -- Chapter 8. Recent Development in the biomarkers for the gastric cancer -- Chapter 9. Gastric Cancer and it's remedy -- Chapter 10. An intergenic variant rs4779584 between SCG5 and GREM1 contributes to the increased risk of colorectal cancer: A meta-analysis -- Chapter 11. Phytochemicals plus nanomaterial's on colorectal cancer -- Chapter 12. Pancreatic Ductal Adenocarcinoma and Type 2 Diabetes Mellitus: Distant Relatives or the Close Ones? -- Chapter 13. Tumor Biomarkers and Diagnosis of Pancreatic Adenocarcinoma -- Chapter 14. Immunotherapy in Gastrointestinal Malignancies -- Chapter 15. The Role of HIF-1ga (Bin Hepatocellular Carcinoma.s
Keywords: Cancer research; Nanotechnology; Radiology; Gene expression; Cancer Research; Nanotechnology; Diagnostic Radiology; Gene Expression